An Exploratory on Factor Influencing of Digital Transformation and Institutionalization in Thai Maritime Industry - Janmethakulwat, Atcharaporn; Thanasopon, Bundit (My University, 2022)
A literature gap exists regarding why Thai maritime industry remain slow to accept new digital transformation to improve the maritime sector's capacity to drive organizational sustainable development. It is essential to understand the determinants factor of digital transformation adoption and continuous to institutionalization change. This study investigates firm level adoption of digital technology and focuses specifically on perceived influence of technology, organization, environment, technology acceptance behavior and commitment factors on the adoption process of digital transformation in Thai maritime industry. Based on an exploration and integration of four adoption related frameworks from technology acceptance use and change management field, a conceptual model linking the intention to use level change to commitment process was created. The model integrates concepts from Technology Acceptance Model (TAM), The Technology, Organization and Environment Framework (TOE framework), Institutional Theory and the model for Institutionalization Change.
Keywords: Digital Transformation; Institutional Theory; Institutionalization; Organization and Environment Framework (TOE framework); Technology Acceptance Model; The Technology